+0  
 
0
69
1
avatar

How to solve |3x - 1| = |2x + 6|.

 Jun 27, 2020
 #1
avatar
0

Solve for x over the real numbers:

1-3 x==-2 (x+3):
1-3 x==2 (x+3) or 1-3 x==-2 (x+3)


Expand out terms of the right hand side:
1-3 x==2 x+6 or 1-3 x==-2 (x+3)


Subtract 2 x+1 from both sides:
-5 x==5 or 1-3 x==-2 (x+3)


Divide both sides by -5:
x==-1 or 1-3 x==-2 (x+3)


Expand out terms of the right hand side:
x==-1 or 1-3 x==-2 x-6


Subtract 1-2 x from both sides:
x==-1 or -x==-7


Multiply both sides by -1:
x==-1     or     x==7

 Jun 27, 2020

52 Online Users

avatar
avatar